Meredith B. McGuire Lived Religion Concept of Santri Waria in Pesantren Al-Fatah Yogyakarta: An Analysis and Application - Nanda Tsani Azizah; Nurkhalis Djilfikar A Hi Daud; Yustina Priskila Patricia Kabes (LPPM STAI AL GAZALI BARRU, 2025)
This paper explores the lived religious experiences of transgender Muslims (santri waria) in Pesantren Al-Fatah, Yogyakarta, using Meredith B. McGuire’s concept of